Marking the Kimmeridgian-Tithonian transition with a bivalve - Protocardia gigantea sp. nov. (Bivalvia: Cardiidae) and its relatives from the Lusitanian Basin (Portugal) - Schneider, Simon; Fürsich, Franz; Werner, Winfried (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2010)
The cardiid Protocardia gigantea sp. nov., which is newly described herein, represents the largest member of this globally distributed genus of shallow-water Mesozoic bivalves. It is found throughout the central Lusitanian Basin (Central Portugal) and may be utilised as a stratigraphie marker for the Kimmeridgian-Tithonian transition in this area, which is confirmed by Sr-isotope data. Its frequent occurrence, large size, and characteristic features make Protocardia gigantea a valuable tool for field stratigraphy. Its taxonomy, systematic position, and ontogenetic as well as intra-population morphological variability are outlined. Possible ancestry in and outside the Lusitanian Basin is discussed, and four other species of Protocardia from the Upper Jurassic of Portugal are taxonomically treated. © 2010 E. Schweizerbart'sche Verlagsbuchhandlung, Stuttgart, Germany.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.markin
Keywords: Cardiidae; Fourier shape analysis; Late jurassic; Morphometry; Portugal; Protocardia; Stratigraphy; Taxonomy